2016
DOI: 10.1097/md.0000000000005548
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter study on the asymmetry of skin temperature in complex regional pain syndrome

Abstract: According to the International Association for the Study of Pain (IASP) and American Medical Association (AMA), the diagnostic criteria for complex regional pain syndrome (CRPS) require the presence of skin temperature asymmetry. In CRPS, it is generally accepted that the temperature of skin of affected limbs changes from warm to cold; however, in our clinical practice, we have experienced many cases with different thermographic characteristics. Therefore, we conducted a retrospective multicenter study that ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Approximately 40–56% of CRPS patients exhibited skin temperature asymmetry in the limbs of greater than 1°C. 25, 47 In a prospective study the average temperature difference between limbs declined over the first year after the onset of CPRS, and the prevalence of skin color changes also decreased, from 95% to 45%. 9 About half of CRPS cases showed warmth and reddening of the affected skin (inflammatory phenotype) in a large multicenter study, while the remaining half had cold, bluish skin (cold phenotype).…”
Section: Comparison Of Crps and Tfm Symptoms Signs And Pathophysiologymentioning
confidence: 99%
“…Approximately 40–56% of CRPS patients exhibited skin temperature asymmetry in the limbs of greater than 1°C. 25, 47 In a prospective study the average temperature difference between limbs declined over the first year after the onset of CPRS, and the prevalence of skin color changes also decreased, from 95% to 45%. 9 About half of CRPS cases showed warmth and reddening of the affected skin (inflammatory phenotype) in a large multicenter study, while the remaining half had cold, bluish skin (cold phenotype).…”
Section: Comparison Of Crps and Tfm Symptoms Signs And Pathophysiologymentioning
confidence: 99%
“…We only studied SkTA in the upper extremity, and it is not clear whether there would be differences in SkTA found in the lower limbs, because this question has not been addressed by other authors employing mixed samples. 35 , 38 Our sample included a spectrum of symptom presentation and duration; however, others have suggested that time course was not a significant predictor of SkTA 35 ; future work should consider whether there are important patterns of symptoms (such as vasomotor changes) that influence or predict skin temperature asymmetry after cold pressor testing. We also did not distinguish between warm and cool subtypes of CRPS, 1 and it is unknown whether the baseline level of vasoconstriction or vasodilation would be an important influence on SkTA.…”
Section: Discussionmentioning
confidence: 98%
“…They reported that 44.3% of their sample did not have a skin temperature asymmetry of greater than 1°C and concluded that symptom chronicity was not an important predictor of SkTA. 35 However, it is also worth noting that their population contained more males and more persons with lower limb CRPS than upper limb CRPS and therefore may not be representative of the broader CRPS population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Thermographic analysis applies in the general case of venous, arterial and lymphatic circulation disorders. 3,4 Thermography has also been used for many years in oncology as an accessory examination in the diagnosis of breast cancer 5 as a method for screening a large group of patients. 6 The effectiveness of histological, mammographic assessment in the diagnosis of early detection of breast cancer was also compared with thermographic studies, 7 as well as with USG tests.…”
Section: Introductionmentioning
confidence: 99%